Perceived discrimination and well-being of unaccompanied refugee minors: The role of ethnic identity - Becker, Jamila Pilar (2020)
There is evidence that minority group members increase their identification with their ethnic groups to cope with perceived discrimination and protect well-being. However, it is yet unknown whether this is also true for unaccompanied refugee minors (URMs), for whom ethnic identity may be disrupted. The present study examined how different sub-dimensions of ethnic identity (i.e., exploration, affirmation, and resolution) mediate the relation between discrimination and psychological well-being (i.e., life satisfaction, depression) among 153 URMs (age 14 to 25 years) in Germany. Results indicated that perceived discrimination was associated positively with depressive symptoms among URMs. Unexpectedly, perceived discrimination was negatively associated with affirmation and resolution, and positively with exploration. Moreover, the relationship between perceived discrimination and life satisfaction was mediated by ethnic identity exploration, suggesting that among the three dimensions, only ethnic identity exploration may protect against the negative consequences of perceived discrimination among URMs in Germany. Practical implications to promote unaccompanied refugee minors’ psychological well-being and to strengthen their ethnic identity are discussed.